2022
DOI: 10.4093/dmj.2021.0135
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Life Span and Severe Hypoglycemia Risk in Postmenopausal Women with Type 2 Diabetes Mellitus

Abstract: Background: Estrogen promotes glucose homeostasis, enhances insulin sensitivity, and maintains counterregulatory responses in recurrent hypoglycemia in women of reproductive age. Postmenopausal women with type 2 diabetes mellitus (T2DM) might be more vulnerable to severe hypoglycemia (SH) events. However, the relationship between reproductive factors and SH occurrence in T2DM remains unelucidated. Methods: This study included data on 181,263 women with postmenopausal T2DM who participated in a national health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…4 Considering the hormonal changes in obese women or women with metabolic syndrome, it is likely that rather than UL itself, the uterus, endometrium, and ovaries might affect the development of type 2 diabetes mellitus. [17][18][19][20] A retrospective population-based cohort study found that the risk of diabetes was higher in women with hysterectomy compared to that in those without hysterectomy (HR 1.37, 95%CI 1.23-1.52) and that diabetes risk was not increased in women with hysterectomy and oophorectomy (HR: 1.28, 95%CI 0.93-1.76). 21 Interestingly, myomectomy seemed to attenuate the risk for type 2 diabetes mellitus in women with UL in our study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Considering the hormonal changes in obese women or women with metabolic syndrome, it is likely that rather than UL itself, the uterus, endometrium, and ovaries might affect the development of type 2 diabetes mellitus. [17][18][19][20] A retrospective population-based cohort study found that the risk of diabetes was higher in women with hysterectomy compared to that in those without hysterectomy (HR 1.37, 95%CI 1.23-1.52) and that diabetes risk was not increased in women with hysterectomy and oophorectomy (HR: 1.28, 95%CI 0.93-1.76). 21 Interestingly, myomectomy seemed to attenuate the risk for type 2 diabetes mellitus in women with UL in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive lifespan represents not only the years during which women can conceive but also the period in which women benefit from estrogen exposure [ 11 ]. The reproductive lifespan has been related to decreased morbidity, decreased mortality, and cardioprotection [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive lifespan is the time period between menarche and menopause, which can reflect the period in which a woman benefits from estrogen exposure [ 11 ]. To date, some cross-sectional studies have explored the association between the reproductive lifespan and the clinical features of PD.…”
Section: Introductionmentioning
confidence: 99%
“…muscular and brain tissue. E 2 also controls the metabolic sensor in the hypothalamus, protecting the brain from hypoglycemia ( 60 ). Otherwise, E 2 potentiates the oxidative capacity of mitochondria and E 2 deprivation induces mitochondrial dysfunction and insulin resistance, mechanisms involved in the development of alterations in cognitive function ( 61 ).…”
Section: Menopause and Development Of Admentioning
confidence: 99%